1981
DOI: 10.1038/bjc.1981.116
|View full text |Cite
|
Sign up to set email alerts
|

Value of serum calcitonin estimation in clinical oncology

Abstract: Summary.-In 132 consecutive patients with carcinoma of various organs, a higher serum immunoreactive calcitonin (ICT) concentration (median level 50 pg/ml) was found than in 68 normal subjects (median level 20 pg/ml). The incidence of hypercalcitoninaemia was 40%o. All 9 patients with primary liver-cell carcinoma were hypercalcitoninaemic. On the other hand, none of the 7 patients with a carcinoma of the breast had raised ICT levels. In bronchogenic cancer a relationship between ICT and cell type was found, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Wallach et al [138] reported a decrease in serum CT levels in SCLC patients responding to chemotherapy, and an increase in progressive diseases. Mulder et al [140], on the contrary, reported no such effect. In conclusion, the assay of serum calcitonin seems to be a general indicator of the course of SCLC disease, but it is sufficiently reliable for evaluating the response to treatment.…”
Section: Hormones As Cancer Biomarkersmentioning
confidence: 80%
“…Wallach et al [138] reported a decrease in serum CT levels in SCLC patients responding to chemotherapy, and an increase in progressive diseases. Mulder et al [140], on the contrary, reported no such effect. In conclusion, the assay of serum calcitonin seems to be a general indicator of the course of SCLC disease, but it is sufficiently reliable for evaluating the response to treatment.…”
Section: Hormones As Cancer Biomarkersmentioning
confidence: 80%
“…WALLACH et al [180] reported a decrease of CT serum levels in SCLC patients responding to chemotherapy, and an increase in progressive diseases. MULDER et al [182], on the contrary, showed no such effect.…”
Section: Calcitoninmentioning
confidence: 89%